2010
DOI: 10.1055/s-0030-1250235
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects ofDendrobiumAlkaloids on Memory Impairment Induced by Lipopolysaccharide in Rats

Abstract: Dendrobium alkaloids (DNLA), extracted from Dendrobium nobile Lindl. whose botanical name is Dendrobium moniliforme, Orchidaceae family, were studied for their effect on lipopolysaccharide (LPS)-induced memory impairment in rats. SD rats were pretreated with DNLA (40, 80, 160 mg/kg/d for 7 d), followed by LPS (50 µg) injection into the right lateral ventricle to produce memory impairment. DNLA treatment continued for another 13 days. The spatial behavior was tested by the Morris water maze; the level of tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 27 publications
2
47
1
Order By: Relevance
“…(DNLA) showed neuro-protective activity. For example, DNLA can prevent neuronal damages induced by LPS (Li et al, 2011; Zhang et al, 2011), and oxygen-glucose deprivation and reperfusion (Wang et al, 2010), decrease neuronal apoptosis, hyperphosphorylation of tau protein (Yang et al, 2014) and A β deposition in rat brain (Chen et al, 2008). The present study aimed to explore the effects of DNLA in protecting neurons from Aβ 25–35 -induced neurotoxicity in mice, and analyzed the mechanism from the aspects of promoting the secretion of neurotrophic factors.…”
Section: Introductionmentioning
confidence: 99%
“…(DNLA) showed neuro-protective activity. For example, DNLA can prevent neuronal damages induced by LPS (Li et al, 2011; Zhang et al, 2011), and oxygen-glucose deprivation and reperfusion (Wang et al, 2010), decrease neuronal apoptosis, hyperphosphorylation of tau protein (Yang et al, 2014) and A β deposition in rat brain (Chen et al, 2008). The present study aimed to explore the effects of DNLA in protecting neurons from Aβ 25–35 -induced neurotoxicity in mice, and analyzed the mechanism from the aspects of promoting the secretion of neurotrophic factors.…”
Section: Introductionmentioning
confidence: 99%
“…In ancient Chinese medical literature dating back over a thousand years, Dendrobium extracts were reported to improve vision [11]; however, there is still no firm understanding of the chemical components and mechanism of these extracts on vision. Recent research indicates that Dendrobium extracts may also have other bioactive properties, including the induction of apoptosis in human gastric cancer cells [12], the facilitation of neuroprotection against stress-induced apoptosis in PC12 cells [13], the inhibition of lipopolysaccharide- (LPS-) induced memory impairment in rats [14], and the LPS-induced nitric oxide production in macrophages [15]. It has also been suggested that Dendrobium extracts have strong antioxidant properties in vitro [16].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, most studies on Dendrobium mainly focus on its tissue culture (Pornpienpakdee et al, 2010;Rangsayatorn, 2009), planting methods (Bichsel et al, 2006) and medicinal compounds (Chang et al, 2010;Li et al, 2011). However, the relationships between species of Dendrobium and their pollinators have rarely been investigated.…”
Section: Introductionmentioning
confidence: 99%